Evaluation of the dynamic sealing performance of cap rocks of underground gas storage under multi-cycle alternating loads - Lidong Mi; Yandong Guo; Yanfeng Li; Daqian Zeng; Chunhua Lu; Guangquan Zhang (Energy Geoscience)
The static sealing of underground gas storage (UGS), including the integrity of cap rocks and the stability of faults, is analyzed from a macro perspective using a comprehensive geological evaluation method. Changes in pore structure, permeability, and mechanical strength of cap rocks under cyclic loads may impact the rock sealing integrity during the injection and recovery phases of UGS. In this work, the mechanical deformation and failure tests of rocks, as well as rock damage tests under alternating loads, are conducted to analyze the changes in the strength and permeability of rocks under multiple-cycle intense injection and recovery of UGS. Additionally, this study proposes an evaluation method for the dynamic sealing performance of UGS cap rocks under multi-cycle alternating loads. The findings suggest that the failure strength (70%) can be used as the critical value for rock failure, thus providing theoretical support for determining the upper limit of operating pressure and the number of injection-recovery cycles for the safe operation of a UGS system.